PERANAN KOMUNIKASI KEPEMIMPINAN DALAM MEMBANGUN KINERJA PEGAWAI KANTOR DINAS PARIWISATA KOTA BUKITTINGGI - Lulu Almaknun; Nunu Burhanuddin (Jurnal Komunikasi, 2023)
The achievements of an organization are identified with its leaders. The leader's job is to guide, influence and encourage members to carry out their tasks and activities to achieve organizational goals. Therefore, leaders are required to have effective communication. In this way, the role of leadership communication plays an important role in the smooth running of the organization. The aim of the research is to determine the role of leadership communication in building employee performance as well as the supporting and inhibiting factors of leadership communication in building employee performance at the Bukittinggi Tourism Office. This research uses a qualitative method with a descriptive qualitative approach. Qualitative data collection techniques use observation methods, interviews with informants using question and answer techniques and dealing directly with informants, and documentation. The research results show that: (1). The role of leadership communication in building the performance of employees at the Bukittinggi City Tourism Office is communicating service policies, providing instructions and tasks clearly and easily understood by employees and motivating employees (2). Supporting factors in the leadership communication process in building the performance of Bukittinggi City Tourism Office employees are good communication skills, mutual trust between employees, sufficient human resources and adequate facilities and infrastructure due to the availability of sufficient APBD funds. The inhibiting factor is the organizational structure system. Because in a structural organizational system the way information, messages or tasks are delivered is also structured